Recent Advances in Molecular Pharmacology of the Histamine Systems: Physiology and Pharmacology of Histamine H3 Receptor: Roles in Feeding Regulation and Therapeutic Potential for Metabolic Disorders - Tokita Shigeru; Takahashi Kazuhiko; Kotani Hidehito (Elsevier, 2006)
Abstract.: Histamine H3 receptors (H3Rs) are autoreceptors that negatively regulate the release of histamine and other neurotransmitters such as norepinephrine, dopamine, and acetylcholine in the central nervous system (CNS). Consistent with the wide-spread projection of histaminergic neurons from the lateral hypothalamus, H3Rs are widely distributed in the CNS and are believed to play a variety of physiological roles, including regulation of feeding, arousal, cognition, pain, and endocrine systems. To further understand the physiological roles of H3Rs in vivo, we produced H3R knockout (H3R−/−) mice and found that H3R−/− mice displayed hyperphagia and late-onset obesity associated with hyperinsulinemia and leptinemia, the fundamental marks of metabolic syndromes. A series of non-imidazole H3R antagonists/inverse agonists with improved selectivity and potency have been developed and were found to regulate feeding and body weight gain in laboratory animals. Taken together, these observations suggest that H3Rs are involved in the regulation of feeding behavior and body weight. Several H3R inverse agonists targeting cognitive disorders and dementia have entered clinical trials. These trials will give critical information about the physiological functions of H3Rs in humans. Keywords:: histamine, histamine H3 receptor, obesity, central nervous system disorder, inverse agonist